Design and development of a wind turbine and fuel cell business case module - Lee, Yi Ren (2014)
Green energy market has been growing for the past half a century, with more emphasis and funds being invested. More so since the sky rocketing price of oil in the early 21st century. This project primarily focuses on the economic breakdown of using fuel cell or wind turbine as the source of power. The end point of this project is coming up with a user friendly platform that is catered for interested parties to access the cost analysis of switching over to fuel cell or wind turbine. The initial part of the project is on researching on the mechanics of fuel cells to derive a mathematical model for estimating the flow rate of fuel used for every level of power output of any fuel cell. The next phase involves collating a database of fuel cell data and building a module via LabVIEW to process the data stored. The final phase is the research and collecting of data of wind turbine within a database followed by integrating a previous FYP student’s LabVIEW module with my collated database.